GAYA BAHASA DALAM NOVEL AYAH KARYA ANDREA HIRATA - Lande, Ester Rindu; Salem, Lauresius; Wastiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the style of danger contained in the novel Father and how the implementation in learning in school. The method used is descriptive method and the research form is qualitative, while the approach used is stylistic approach. Based on the results of data analysis, the following conclusions are derived: 1) the comparative language style contained in the 186 novel Ayah, which includes 47 personifications, 47 hyperbola f pieces, 24 similes, 53 pieces metaphors, 2 pieces sinekdoke, 2 pieces pleonasme, euphemism 5 pieces, 2 pieces synesthesia and metonimia 4 pieces. 2) the style of contradiction in the novel Ayah numbered 12 pieces, namely the paradox amounted to 6 pieces, antithesis 5 pieces, and koreksio 1 pieces. 3) the style of affirmation in the novel Ayah amounted to 39 pieces, including tautology 2 pieces, asidenton 8 pieces, climax 6 Â pieces and reps 23 pieces. 4) language style satire in the novel by Andrea Hirata's father amounted to 2 pieces namely, cynicism 1 pieces and sarcasm 1 pieces. The language style contained in Andrea Hirata's father's novel is 239 in total and the most dominant language style is the comparative language style, which is a metaphor of 53 pieces. For learners, the results of this study can provide science in literary works, especially the style of language in the novel. This study is also useful for the reader to distinguish the author's language style in writing novels.Â Keywords: style of language, novel